The Influence of Personal Relationships and Work Programs on Village Heads' Decisions in Choosing Regent Candidates in West Lombok with Trust as Mediation - Sudirman Sudirman; Baiq Handayani Rinuastuti; Handry Sudiartha Athar (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of personal relationships and work programs on village heads' decisions in choosing regent candidates in West Lombok, with trust as a mediating variable. The research method used is quantitative by distributing questionnaires to village heads as respondents, and the data is analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) model. The results showed that personal relationships and work programs have a significant positive effect on trust, and have a direct and indirect effect on voting decisions through trust as mediation. This finding indicates that trust is a strategic factor that strengthens the influence of personal relationships and work programs in the political decision-making process at the village level